Implementation of Digital Marketing as a Business Recovery Strategy for Micro, Small and Medium Enterprises in Medan Area - Nainggolan, Elisabeth; Pesta Gultom; Desma Erica Maryati Manik (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2022)
The dynamics of global economic development is currently undergoing a paradigm shift where the resource-based economy becomes a knowledge and creativity-based economy or known as the creative economy. The creative economy is growing rapidly, supported by advances in information technology that produces information media such as the internet. The internet has become a means to meet the needs of the community in running their business, one of which is used for marketing or what is known as digital marketing. The right digital marketing strategy can be used to reach the targeted market segment so that it can increase profits for businesses and increase income for business actors. This study aims to analyze the influence of Digital Marketing and Business Capital on the Income of MSME actors in the Medan Area District. This type of research is quantitative research. The population in this study were all MSME actors in the District of Medan Area with an undetermined or uncertain number. By using the Hair formula, the maximum number of samples is 100 respondents. In this study, the number of samples was 96 respondents. The data used in this study is primary data obtained through the distribution of questionnaires to MSME actors in the Medan Area District. The data analysis technique applied in this study is multiple linear regression analysis using SPSS version 23 as a data processing tool